Regionaltågstrafikens effekter: En studie av regionaltågslinjer i Skåne - Sahlin, Hans Svensson (Proceedings from the Annual Transport Conference at Aalborg University, 2011)
The focus of this project is on the effects of regional train traffic consisting of Pågatåg and Öresund trains in Skåne, Sweden. The principal effects studied are travelling/commuting by train, population trends in the suburban areas around stations, population distribution in Skåne compared to the rest of the country, development of the labour market regions, changes in the educational level in Skåne compared to the rest of the country, and property price trends after the introduction of regional trains.